Find the inverse of f(x)= (x-3)/(x+2) and f(x)= (8x-4)/(2x+6).

2 answers

Here's how to do the first one.
(1) solve for x in terms of y. x = f(y)
(2) switch variables x and y.
y = (x-3)/(x+2)
xy + 2y = x - 3
x(y-1) = -3 -2y
x = (2y+3)/(1-y)
The inverse function is
f^-1 (x) = (2x+3)/(1-x)

Do the second problem the same way.
56562
Similar Questions
  1. 1. Let f(x)=x^5 + 2x^3 + x - 1Find f^-1(3) and (f^-1)'(3)? I have zero idea how to find the inverse of this function at a point
    1. answers icon 1 answer
  2. Find inverse of f if f(x)= x^2-4x+3, (for x is smaller than and equal to 2).First prove that f(x) is one to one in the defined
    1. answers icon 1 answer
    1. answers icon 7 answers
  3. Find the inverse of g(x)=(1/3x)-7 and then find its domain and range.I already found the inverse of the function.
    1. answers icon 1 answer
more similar questions